2007
DOI: 10.1111/j.1745-6916.2007.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical Systems Approach to the Development and Expression of Female Same-Sex Sexuality

Abstract: Researchers have documented substantial variability in the development and expression of same-sex sexuality, especially among women, posing challenges to traditional linear developmental models. In this article, I argue for a new approach to conceptualizing the development and expression of female same-sex sexuality over the life course, based in dynamical systems theory. Dynamical systems models seek to explain how complex patterns emerge, stabilize, change, and restabilize over time. Although originally deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
80
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 107 publications
(170 reference statements)
7
80
1
1
Order By: Relevance
“…For example, subsequent studies found that LGB youth report shifts in their sexual attractions, behaviors, and identities over time (Diamond, 2005;Ott, Corliss, Wypij, Rosario, & Austin, 2011;Savin-Williams & Ream, 2007). Also, individuals who self-identified as lesbian do not always exclusively report same-sex attraction and some state that their sexual attractions changed over time (Diamond, 2007).…”
Section: Stability/mobility In Sexual Orientationmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, subsequent studies found that LGB youth report shifts in their sexual attractions, behaviors, and identities over time (Diamond, 2005;Ott, Corliss, Wypij, Rosario, & Austin, 2011;Savin-Williams & Ream, 2007). Also, individuals who self-identified as lesbian do not always exclusively report same-sex attraction and some state that their sexual attractions changed over time (Diamond, 2007).…”
Section: Stability/mobility In Sexual Orientationmentioning
confidence: 97%
“…Diamond (2007) explored this question asking a sample of women to self-identify their sexual identity over a 10-year period. Diamond found that many of the women changed their identity labels but that the majority did not make such changes in a transitional fashion of going from a bisexual to lesbian identity.…”
Section: Stability/mobility In Sexual Orientationmentioning
confidence: 99%
“…For example, adult women appear likely to report sizeable discrepancies among their attractions, romantic feelings, and sexual behaviors; to report a markedly late and abrupt onset of same-sex sexuality, often after heterosexual marriage (Cassingham & O'Neil, 1993;Walsh, 2010); to report fluctuations in their sexual behaviors and identities over time, sometimes triggered by single relationships (see reviews in Baumeister, 2000;Diamond, 2003bDiamond, , 2007Diamond, , 2008Hyde, 2005;Mustanski et al, 2002;Peplau, 2001;Peplau & Garnets, 2000).…”
mentioning
confidence: 97%
“…In light of these robust sex differences, some have gone so far as to argue that sexual orientation might not even exist in women (Bailey, 2009), whereas others have argued that it unfolds and operates in a less deterministic fashion for women than for men (Peplau, 2001) or interacts dynamically with a general propensity for female erotic plasticity or fluidity (Baumeister, 2000;Diamond, 2007). In essence, the''compass''analogy for sexual orientation does not work well for women: What, then, is the right model?…”
mentioning
confidence: 98%
“…As we noted in our article, studies have shown considerable fluidity in the development and expression of sexual behavior and orientation over time, particularly in young women (Diamond, 2005(Diamond, , 2007(Diamond, , 2008Diamond & Butterworth, 2008). The current comparison of 17-year-olds in the 6th and 7th cycles of the NSFG suggests that further exploration of factors that may be contributing to changing patterns of same-sex sexual behavior in American adolescents is warranted.…”
mentioning
confidence: 63%